Assessing patient satisfaction in gastrointestinal endoscopy: Development and validation of the Turkish GESQ for quality improvement - Ali Karataş; Kenan Moral; Yunus Emre Börü; Dilek Yapar; Rukiye Sarıgül; Ayfer Akgün; Yağmur Eken; Beril Demir; Halit Kandemir; Enes Cömert; Derya Kirman; Gülden Bilican; et al. (Akademik Gastroenteroloji Dergisi, 2026)
Background and Aims: Patient satisfaction has become an essential quality indicator in gastrointestinal endoscopy, complementing traditional performance measures such as adenoma detection and cecal intubation rates. The Gastrointestinal Endoscopy Satisfaction Questionnaire is a validated tool widely used to assess patient satisfaction across multiple domains. However, a culturally adapted Turkish version has been lacking. This study aimed to translate, culturally adapt, and validate the Turkish version of the Gastrointestinal Endoscopy Satisfaction Questionnaire to evaluate patient satisfaction with gastrointestinal endoscopic procedures in Türkiye. Materials and Methods: This Methodological Study included 178 adult patients undergoing upper and/or lower endoscopy at a tertiary academic center between July 2025 and September 2025. The original Gastrointestinal Endoscopy Satisfaction Questionnaire was translated and back-translated following established cross-cultural adaptation guidelines. Exploratory factor analysis using principal component extraction with Varimax rotation was performed to evaluate construct validity. Internal consistency was assessed using Cronbach’s alpha coefficients. Spearman’s correlation analysis was applied to examine inter-domain relationships. Results: The final 20-item Turkish version of the Gastrointestinal Endoscopy Satisfaction Questionnaire demonstrated a four-factor structure , Information before endoscopy, Pain or discomfort during/after endoscopy, Information after endoscopy, and Skills and hospital, accounting for 53.3% of total variance. Cronbach’s α ranged from 0.639 to 0.812 across subscales, with an overall α = 0.820, indicating acceptable reliability. Weak to moderate positive correlations among the subscales supported the construct validity of the scale. Conclusion: The Turkish version of the Gastrointestinal Endoscopy Satisfaction Questionnaire is a valid and reliable instrument for assessing patient satisfaction with gastrointestinal endoscopy. Its implementation can facilitate benchmarking, quality improvement, and integration of patient-reported outcomes into endoscopy quality assurance